The Impact of Blockchain Technology Implementation on Financial Reporting Transparency and Efficiency - Hamzah, Muhammad Luthfi; Hamzah, Zulfadli; Najima, Najima (Research in Accounting Journal (RAJ), 2024)
This study examines the impact of blockchain technology on financial reporting, focusing on its effects on transparency, efficiency, and audit quality. The research utilized both qualitative (semi-structured interviews) and quantitative (surveys) methods to gather data from professionals in the field of accounting and finance. The qualitative findings suggest that blockchain enhances transparency and efficiency in financial reporting processes, particularly through its immutable ledger and real-time access to transaction data. Additionally, it was found that blockchain improves audit quality by providing auditors with more reliable and verifiable data. However, the study also identified significant barriers to blockchain adoption, including regulatory uncertainty, high implementation costs, and technical integration challenges. The survey results, based on 100 respondents, confirmed these findings, with 85% agreeing that blockchain improves transparency and 78% believing it enhances efficiency. Despite these benefits, 68% of respondents cited regulatory uncertainty as a key barrier to adoption. This study contributes to the literature on blockchain's role in financial reporting and offers insights into the challenges and opportunities for blockchain implementation in the accounting and auditing fields.